The Effect of Audit Tenure, Audit Rotation, and Audit Delay on Audit Quality with Audit Committee as a Moderating Variable - Muhamad Tabsyir; Muhsin; Khristina Yunita (Institut Bisnis dan Informatika Kesatuan, 2025)
In today’s digital era, where information is rapidly accessible, ensuring precise and reliable financial reporting is vital for sustaining stakeholder trust. However, limited research has examined how auditor-related factors such as auditor tenure, auditor rotation, and audit delay interact with corporate governance mechanisms to influence financial reporting quality. This study investigates the effects of auditor tenure, auditor change, and audit completion time on audit quality, while assessing the moderating effect of the audit committee as a key element of corporate governance. Using secondary data from food and beverage companies listed on the Indonesia Stock Exchange (IDX) between 2021 and 2023, analyzed with moderated regression analysis (MRA), the findings reveal that auditor tenure does not significantly affect audit quality. In contrast, auditor rotation and audit delays have negative impacts. Moreover, the audit committee mitigates the adverse effect of prolonged auditor tenure but does not influence the negative consequences of auditor rotation or delay. This study contributes new empirical evidence from an emerging market context, emphasizing the critical role of audit committees in strengthening corporate governance and maintaining financial reporting quality. The findings provide important insights for corporate leaders and regulators in improving audit oversight.